1998
DOI: 10.1080/001401398186829
|View full text |Cite
|
Sign up to set email alerts
|

Physiological workload reactions to increasing levels of task difficulty

Abstract: The sensitivity of physiological measures to mental workload was investigated in a flight simulator. Twelve pilots had to fly through a tunnel with varying levels of difficulty. Additionally, they had to perform a memory task with four levels of difficulty. The easiest memory task was combined with the easiest tunnel task and the most difficult memory task with the most difficult tunnel task. Between the tunnel tasks, subjects had to fly a pursuit task in which a target jet had to be followed. Rest periods bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
235
5
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 354 publications
(258 citation statements)
references
References 11 publications
16
235
5
2
Order By: Relevance
“…Some authors have argued that HRV is a more sensitive measure of learners' physiological arousal compared to heart rate. [33][34] However, our group has previously found that actual heart rate is more sensitive than HRV as a measure of learners' arousal. 8 Also, while serum cortisol, measured through saliva, has been identified as a valid and reliable reflection of physiological stress, 35,36 repeated measures of salivary cortisol at all testing sessions would have been fairly costly to collect given our large sample size.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have argued that HRV is a more sensitive measure of learners' physiological arousal compared to heart rate. [33][34] However, our group has previously found that actual heart rate is more sensitive than HRV as a measure of learners' arousal. 8 Also, while serum cortisol, measured through saliva, has been identified as a valid and reliable reflection of physiological stress, 35,36 repeated measures of salivary cortisol at all testing sessions would have been fairly costly to collect given our large sample size.…”
Section: Discussionmentioning
confidence: 97%
“…We performed moving-window analyses on blink and saccade frequency, as well as on saccade directions. Blink frequency is known to decrease when concentrated effort is needed to perform a task or`to uptake' information (eg De Jong and Merckelbach 1990;Zangemeister et al 1995;Veltman and Gaillard 1998). Blink frequency is used in the present study as a measure of effort.…”
Section: Time Seriesmentioning
confidence: 99%
“…A consequence of the second option is that the workload will remain the same but that the overall level of performance increases. To investigate the effects of 3-D audio on mental workload more thoroughly, several physiological measurements that are related to mental workload (see Veltman & Gaillard, 1998) as well as subjective effort ratings were included in the present study.…”
Section: The Present Experimentsmentioning
confidence: 99%